Effect of pH on the photocatalytic degradation of remazol brilliant blue dye using zirconia catalyst - Muhammad Farhan, Hanafi; Norzahir, Sapawe (Elsevier, 2020)
EGZrO2 catalyst was successfully synthesized using electrochemical method with an established of photocatalytic activity evaluation. An amount of 0.20 g/L of EGZrO2 catalyst was found to provide the optimum dosage for 10 mg/L remazol brilliant blue (RBB) dye resulting in a complete degradation (99.8%) within 1.5 h of contact time. The catalyst showed good performance in pH 3 (acidic medium) due to the influence of surface charge properties (amphoteric behavior). The excellence photoresponse in visible light regions gave advantage to the photoreaction which is cost effective, practicable, and more eco-friendliness.